2013
DOI: 10.1007/s10858-013-9721-2
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state NMR enhanced by dynamic nuclear polarization as a novel tool for ribosome structural biology

Abstract: The impact of Nuclear Magnetic Resonance (NMR) on studies of large macromolecular complexes hinges on improvements in sensitivity and resolution. Dynamic nuclear polarization (DNP) in the solid state can offer improved sensitivity, provided sample preparation is optimized to preserve spectral resolution. For a few nanomoles of intact ribosomes and an 800 kDa ribosomal complex we demonstrate that the combination of DNP and magic-angle spinning NMR (MAS-NMR) allows one to overcome current sensitivity limitations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
54
0
1

Year Published

2015
2015
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 55 publications
0
54
0
1
Order By: Relevance
“…studied by conventional ssNMR can be down to even $ 30 Hz (with specific isotopic labeling) [48], attributable to high crystallinity or fast conformational averaging. However, dissolution or suspension of the biomolecular analyte in frozen DNP matrices can increase this value to a few hundreds of Hz due to inhomogeneous broadening, leading to a decrease in resolution [49][50][51][52][53][54]. Just cooling the biological sample to low temperatures, in the absence of DNP matrices, can produce extensive inhomogeneous broadening as various conformers are trapped, especially in areas of high solvation level and mobility at RT [55].…”
Section: Resolutionmentioning
confidence: 99%
“…studied by conventional ssNMR can be down to even $ 30 Hz (with specific isotopic labeling) [48], attributable to high crystallinity or fast conformational averaging. However, dissolution or suspension of the biomolecular analyte in frozen DNP matrices can increase this value to a few hundreds of Hz due to inhomogeneous broadening, leading to a decrease in resolution [49][50][51][52][53][54]. Just cooling the biological sample to low temperatures, in the absence of DNP matrices, can produce extensive inhomogeneous broadening as various conformers are trapped, especially in areas of high solvation level and mobility at RT [55].…”
Section: Resolutionmentioning
confidence: 99%
“…A N6-C6 (151). The enhancement (ε ∼ 25) and resolution enable the assignment of many residues at a cryogenic temperature of 100 K, for example, the threonine and alanine sites.…”
Section: Whole Cells Plant Cells and Other Biomacromoleculesmentioning
confidence: 99%
“…Transmission electron microscopy (TEM) revealed that the nanoparticles have an average size of 2.0 nm (Figure 1 b). The capping of the nanoparticles is confirmed by 1 H NMR spectroscopy using the following experiment. When glutathione is dissolved in solution, narrow resonance signals attributable to the functional groups in the molecule are detected (Figure 1 c, top spectrum).…”
mentioning
confidence: 98%
“…These substantial signal enhancements facilitate detection of molecules in low concentrations. Hyperpolarization implicates a wide range of applications, from structural biology [1][2][3] to quantum computation, [4] operando investigations of catalytic reactors, [5,6] molecular imaging, and in vivo diagnostics. [7][8][9][10][11][12][13] The para-hydrogen-induced polarization (PHIP) method utilizes the singlet spin order of para-hydrogen to create hyperpolarization by incorporating hydrogen from parahydrogen into a molecule of interest, or by a catalystmediated, reversible exchange process.…”
mentioning
confidence: 99%
See 1 more Smart Citation